2018
DOI: 10.1017/s1368980018000289
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent perspectives of the recreational ice hockey food environment and influences on eating behaviour revealed through photovoice

Abstract: Results indicate recreation facilities are only one of a range of environments that influence eating behaviours of adolescent ice hockey players. Players' susceptibility to advertising/brand promotion and the value of healthy food choices for performance are findings that can inform policy and interventions to support healthy environments and behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 64 publications
1
34
0
Order By: Relevance
“…These findings also support the multidimensionality of food choice among adolescents in general [ 66 ] and athletes in particular [ 67 ]. The gap between knowing what to include in a dietary plan and the actual foods consumed may be due to limited healthy food availability at home [ 68 ], school [ 66 , 69 ] or in the sport environment [ 16 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings also support the multidimensionality of food choice among adolescents in general [ 66 ] and athletes in particular [ 67 ]. The gap between knowing what to include in a dietary plan and the actual foods consumed may be due to limited healthy food availability at home [ 68 ], school [ 66 , 69 ] or in the sport environment [ 16 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2016–2017, over 24,000 HS students played soccer [ 13 ]. Unfortunately, adolescent athletes do not always make healthful food choices [ 14 , 15 ] or have the best food options available to them at sporting events [ 16 ]. Active youth, especially those engaged in intense sport participation, have unique energy and nutritional needs [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…As for food company sponsorship, found that most children aged 10-11 years could recall the sponsor of their sports team, held favorable views about this sponsor and said they would like to buy the sponsor's products to "return the favour" [14]. Similarly, a Canadian study investigating the food experiences of adolescent hockey players revealed that Tim Hortons' (a large coffee/donut chain) sponsorship of their childhood hockey team had fostered sentiments of loyalty among these youth as well as a desire to support the restaurant in return [35]. In addition to sponsorship, two companies, namely Danone and McDonalds, were also identified as using professional athletes as ambassadors for their initiatives.…”
Section: Csr Initiatives and Childrenmentioning
confidence: 99%
“…The majority (about two-thirds) of students in our study stated that they rarely or never ate food from a vending machine, although about 13 percent did so at least once a week. Further work is required to ensure healthy eating habits among students by improving the nutritional quality of products available for sale in these machines both within schools and in other settings, like recreation facilities, where children spend time [42].…”
Section: Discussionmentioning
confidence: 99%